PENGARUH PENGALAMAN KERJA, BEBAN KERJA DAN MOTIVASI TERHADAP KINERJA GURU DI SMK NEGERI KABUPATEN BIREUEN - Amri, Amri; Kamaruddin, Kamaruddin (LPPM-UNIKI, 2023)
The research was conducted on State Vocational School teachers in Bireuen Regency, with the aim of knowing the effect of work experience, workload and motivation on teacher performance either partially or simultaneously. Using quantitative research methods with descriptive and verification analysis. Data obtained based on a survey with a questionnaire instrument that is measured. And statistical data analysis techniques with a path model approach (Path Models). The research results are known, (1). there is a significant correlational relationship between the exogenous variables (work experience, workload and teacher motivation). (2). Through the F-test and t-test it is proven that there is a direct effect of all exogenous variables (work experience, workload and teacher motivation) on endogenous variables (teacher performance). (3). The direct and indirect influence of work experience on teacher performance is 25.04%. (4). The direct and indirect effect of workload on teacher performance is 27.17%. (5). The direct and indirect influence of work motivation on teacher performance is 25.4%. (6) Simultaneously work experience, workload and motivation contribute to teacher performance at SMK Negeri Bireuen Regency by 58.3%. And the remaining 41.7% is the role of variables not examined, such as work culture, environment, competence and others